2017
DOI: 10.1038/s41528-017-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

On the unipolarity of charge transport in methanofullerene diodes

Abstract: Fullerenes are electron transporting organic semiconductors with a wide range of applications. In particular, methanofullerenes have been the preferred choice for solution-processed solar cells and photodiodes. The wide applicability of fullerenes as both ‘n-type’ transport materials and electron acceptors is clear. However, what is still a matter of debate is whether the fullerenes can also support efficient transport of holes, particularly in diode geometries. In this letter, we utilize a number of recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Interestingly, D18 exhibited prominent hole extraction but a negligible signal from the electron-based devices, indicating a typical unipolar charge transport property. 35 The calculated hole mobility is 1.2 × 10 −3 cm 2 V −1 s −1 , which is almost identical to the TRMC result.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, D18 exhibited prominent hole extraction but a negligible signal from the electron-based devices, indicating a typical unipolar charge transport property. 35 The calculated hole mobility is 1.2 × 10 −3 cm 2 V −1 s −1 , which is almost identical to the TRMC result.…”
Section: Resultssupporting
confidence: 80%
“…Panels e and f of Figure display the MIS-CELIV transient current of the hole and electron devices at offset voltages of 0 and 1 V, respectively. Interestingly, D18 exhibited prominent hole extraction but a negligible signal from the electron-based devices, indicating a typical unipolar charge transport property . The calculated hole mobility is 1.2 × 10 –3 cm 2 V –1 s –1 , which is almost identical to the TRMC result.…”
Section: Results and Discussionsupporting
confidence: 67%
“…These traps define an energetic window for bipolar trap-free charge transport in organic semiconductors: if the lowest unoccupied molecular orbital (LUMO) [or highest occupied molecular orbital (HOMO)] lies above [below] the electron [hole] trap level, the electron [hole] transport is inevitably trap-limited. This explains the unipolarity of long-range charge transport in most organic semiconductors at low carrier densities 8,10 . However, we note that a different conclusion was reached in a recent study by Zuo et al who suggested that the traps are caused by water-filled nanovoids, inducing trap levels that are always~0.3-0.4 eV above (below) the HOMO (LUMO) 11 .…”
mentioning
confidence: 86%
“…In a field-effect transistor at high gate bias, charge-carrier densities are high, which obscures the presence of bulk traps or tail states to a certain degree [19]. By contrast, at low carrier densities in a diode configuration, measurements of the bulk mobility in [60]PCBM and [70]PCBM showed highly unipolar transport, with hole mobilities more than 6 orders of magnitude lower than the electron mobilities [20], comparable to what has been observed for C 60 thin films [15][16][17]. It should be noted that for charge-transport characterization in a diode configuration Ohmic contacts are of critical importance.…”
mentioning
confidence: 99%